2017
DOI: 10.1186/s12896-017-0354-5
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a novel anaerobic pathway in Escherichia coli for propionate production

Abstract: BackgroundPropionate is widely used as an important preservative and important chemical intermediate for synthesis of cellulose fibers, herbicides, perfumes and pharmaceuticals. Biosynthetic propionate has mainly been produced by Propionibacterium, which has various limitations for industrial application.ResultsIn this study, we engineered E. coli by combining reduced TCA cycle with the native sleeping beauty mutase (Sbm) cycle to construct a redox balanced and energy viable fermentation pathway for anaerobic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Cells were grown in complex media 0.73 Srirangan et al (2013) Propionate production was achieved by expressing the sbm operon and the methylmalonyl-CoA mutase from Methylobacterium extorquens AM1. Cells were grown in complex media 3.42-70.57 Li et al (2017) Propionate production was achieved by expressing the sbm operon and the methylmalonyl-CoA epimerase from Propionibacterium acidipropionici.…”
Section: Propionate Titer MM Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were grown in complex media 0.73 Srirangan et al (2013) Propionate production was achieved by expressing the sbm operon and the methylmalonyl-CoA mutase from Methylobacterium extorquens AM1. Cells were grown in complex media 3.42-70.57 Li et al (2017) Propionate production was achieved by expressing the sbm operon and the methylmalonyl-CoA epimerase from Propionibacterium acidipropionici.…”
Section: Propionate Titer MM Referencesmentioning
confidence: 99%
“…The first one used the native silent "sleeping beauty mutase (sbm)" operon (Haller, Buckel, Rétey, & Gerlt, 2000). The pathway was completed with a methylmalonyl-CoA mutase from Methylobacterium extorquens AM1 and expressed in a succinate overproducing strain to improve production (Li et al, 2017). Recently, we showed that the coexpression of a methylmalonyl-CoA epimerase allowed for propionate production in a chemically defined medium under aerobic and anaerobic conditions (Gonzalez-Garcia, McCubbin, Wille et al, 2017).…”
mentioning
confidence: 99%
“…MCM catalyzes the interconversion of (R)-methylmalonyl-CoA and succinyl-CoA, a bidirectional reaction used in propionate metabolism [12,75,76], catabolism of branched amino acids and odd-chain fatty acids [76,77], polyhydroxybutyrate degradation [78], secondary metabolite biosynthesis [79], and autotrophic carbon dioxide fixation [4,80]. MCM-dependent pathways have been harnessed industrially for the bioproduction of propionate, bioplastics, biofuels, and antibiotics [81][82][83][84][85][86][87][88].…”
Section: Introductionmentioning
confidence: 99%
“…MCM catalyzes the interconversion of (R)-methylmalonyl-CoA and succinyl-CoA, a bidirectional reaction used in propionate metabolism (Hosotani et al, 1980;Savvi et al, 2008;Vrijbloed et al, 1999), catabolism of branched amino acids and odd-chain fatty acids (Fenton et al, 2014;Savvi et al, 2008), polyhydroxybutyrate degradation (Charles et al, 1997), secondary metabolite biosynthesis (Hunaiti and Kolattukudy, 1984), and autotrophic carbon dioxide fixation (Berg et al, 2007;Han et al, 2012). MCM-dependent pathways have been harnessed industrially for the bioproduction of propionate, bioplastics, biofuels, and antibiotics (Akawi et al, 2015;Aldor et al, 2002;Dayem et al, 2002;Gonzalez-Garcia et al, 2017;Gross et al, 2006;Li et al, 2017;Reeves et al, 2007;Srirangan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the many products that have been produced in E. coli, PA was first produced in E. coli by Kandasamy et al [ 6 ] using the acrylate pathway. More recently, several investigations have reported PA production using the silent native operon known as the sleeping beauty mutase, sbm [ 18 22 ]. The sbm operon encodes four enzymes, three of them allegedly able to complete a succinate dissimilation cycle: methylmalonyl-CoA mutase (ScpA), biotin-independent methylmalonyl-CoA carboxylase (ScpB), and propionyl-CoA:succinate CoA transferase (ScpC) (Fig.…”
Section: Introductionmentioning
confidence: 99%